Recent advancements in Uracil and 5-Fluorouracil hybrids as potential anticancer agents: A review - Mohit Sanduja, Jyoti Gupta, Tarun Virmani (Journal of Applied Pharmaceutical Science, 2020)
Cancer is the most dreadful disease and the second main cause of death worldwide. The continuous developments have been going on in order to design potent molecules such that this leading cause of death can be dealt with. In order to decrease the level of toxicity and to improve the selectivity of drugs toward cancer targets, the development of hybrid molecules has become the center of research, and scientists are doing timeless efforts to generate such a hybrid which has got no comparison with the previous developments. The heterocyclic moiety Uracil and many of its derivatives were already exposed as promising anticancer agents. Moreover, coupling of Uracil and 5-Fluorouracil (5-FU) with different pharmacophores has been proven to be an excellent strategy against cancer. Hence, the present review is an effort to collectively represent all the earlier and recent developments of Uracil and 5-FU hybrids reported to have a significant anticancer profile. Expectantly, we can assure that this article can serve as the basis for further developments in Uracil and 5-FU hybrids and will surely motivate the medicinal chemists for producing unique anticancer drug.
Keywords: Uracil, 5-Fluorouracil, cancer, hybrid, anticancer agents, cell lines.